Methods and applications of statistics in clinical trials - Balakrishnan, N., 1956- (Methods and applications of statistics, 2014)
"This comprehensive book features both new and established material on the key statistical principles and concepts for designing modern-day clinical trials, such as hazard ratio, flexible designs, confounding, covariates, missing data, and longitudinal data. It discusses the various kinds of trials that can be found in today's clinical setting including open-labeled trials, multicentered trials, and superiority trials. It also explores such ongoing, cutting-edge trials as early cancer & heart disease, mother to child human immunodeficiency virus transmission, women's health initiative dietary, and AIDS"--Provided by publisher.